DESIGN OF DOUBLE-EGG CURVE IN THE LINK ROADS OF TRANSPORTATION NETWORKS - Koc, Ibrahim; Gumus, Kutalmis; Selbesoglu, Mahmut Oguz (UNIV OSIJEK, TECH FAC, 2015)
The turns from highways to settlement areas are achieved by link roads. For the safety of these turns, turning radii are required to be large. However, it is not always possible to achieve these turnings by means of arcs of circle with large radius, as different factors, such as topography, the state of settlement, problems impossible to overcome and economic conditions, do not allow designing such a route. Instead, for the sake of traffic, linear variation of the line curvature or maintaining the line curvature at constant value is highly desirable. One of the line geometries is the clothoid egg curve. Single and double type clothoid egg curves are used in many applications. In this study, the calculation and design of double-egg curve are explained by equations and figures in detail. For the design of two egg curves used in rotation from main road to connecting road in transportation networks as application, an example is provided for a better understanding of the subject. The main points of rotation geometry with the coordinates of auxiliary points and other intermediate results are given in a table. The main purpose of this study, the theory and calculations of two egg curves will provide basis to practitioners on a sample in a detailed way. By the fulfilment of design and its calculation of this rotation geometry which provides safer and more comfortable driving, it is hoped to be useful for practitioners.
Keywords: clothoid; curvature; double-egg curve; egg curve; length of transition curve; Engineering